Morphological and crystalline evolution of Sm-(20 mol%)–doped ceria nanopowders prepared by a combined co-precipitation/hydrothermal synthesis for solid oxide fuel cell applications. Issue 15 (15th October 2017) - Dell'Agli, G.; Spiridigliozzi, L.; Marocco, A.; Accardo, G.; Frattini, D.; Kwon, Y.; Yoon, S.P.
Abstract: Nanocrystalline Samarium (20 mol%)-doped ceria (SDC20) nanopowders were prepared using a combined co-precipitation/hydrothermal treatment synthesis route carried out at reduced temperature (120 °C). The amorphous precursor experiences some microstructural transformations during the hydrothermal treatment, and after 16 h a Samarium-Cerium hydroxide carbonate, characterized by a hexagonal crystalline lattice, spherical morphology and particles of about 100 nm in size, with a very low degree of agglomeration, is the only present phase in contrast to the initial amorphous state. After the calcination step, the powders which preserved this morphology are still characterized by the absence of hard agglomerates. As a consequence, these powders exhibited an excellent sintering behaviour with a microstructure characterized by regular, equiaxed and micrometric grain size. In fact, at 1500 °C a nearly perfect densified sample was obtained, but also at 1300 °C a very good sintering behaviour was observed. Finally, the electrochemical characterization carried out by EIS measurements showed a very good electrical behaviour with high ionic conductivity, i.e. at 800 °C 5.2·10 −2  S cm −1 and 4.8·10 −2  S cm −1 for pellets sintered at 1500 °C and 1300 °C respectively, making them suitable for IT-SOFCs. Graphical abstract: